2012
DOI: 10.1117/12.914846
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced thermal dynamics and temperature localization phenomenon in tissues and cells doped with nanoshells

Abstract: Paper presents and discusses the features of laser-induced thermal dynamics of the gold nanoshells, which is associated with their relatively large size and layered structure. Unlike bulk nanoparticles the existence of a novel thermal phenomenon − hoop-shaped narrow hot zone on the nanoshell surface − is found. It is caused by spatial-temporal inhomogeneities of light field diffracted by a nanoshell and corresponding absorption of laser radiation. The numerical solution of time-dependent heat conduction equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To calculate the temperature evolution of the particle during and after the interaction with the laser pulse, we numerically solve the heat transfer Eq. (3) [41,42]. Fig.…”
Section: Nanosecond Pulse Laser Illuminationmentioning
confidence: 91%
“…To calculate the temperature evolution of the particle during and after the interaction with the laser pulse, we numerically solve the heat transfer Eq. (3) [41,42]. Fig.…”
Section: Nanosecond Pulse Laser Illuminationmentioning
confidence: 91%
“…In recent years, nanoparticles have attracted wide attention in the field of biomedicine due to their unique physical, chemical and biological properties. For example, carbon nanotubes, fullerenes, spherical polystyrene, various metals and metal oxide nanoparticles have been extensively studied (Parashar et al 2008, Terentyuk et al 2012, Yakunin et al 2012. Zinc oxide nanoparticles (ZnO NPs) have been widely utilized in drug delivery antibacterial materials, sunscreens, cosmetics, and electronics (Kisin et al 2007, Robertson et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have shown that some nanoparticles can be used for optical imaging of biological tissue to provide better image quality and diseases detection capability [1][2][3][4][5]. Carbon nanotubes, fullerenes, spherical polystyrene, various metals, and metal oxide nanoparticles are widely examined [6][7][8]. They have been successfully utilized Laser Physics Letters Effect of differently sized nanoparticles' accumulation on the optical properties of ex vivo normal and adenomatous human colon tissue with OCT imaging and diffuse reflectance spectra Yang 3 , Y H He 4 , S S Xie 3 and Y Liu 1 in many medical imaging techniques, such as ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI [9]).…”
Section: Introductionmentioning
confidence: 99%